1985
DOI: 10.1111/j.1744-7348.1985.tb03108.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of leaf growth in sugar beet.

Abstract: The influence of season, and certain agronomic treatments (irrigation, nitrogen fertiliser, density of planting and sowing date) on leaf number were analysed in a series of sugar-beet crops grown during the five seasons 1978-82. Leaf appearance was a linear function of thermal time (accumulated temperature above 1 "C) and could be described by four variables: a) the thermal duration of the seedling establishment phase, d's; b) the thermal time interval between appearance of each of the early leaves, Be; c) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 21 publications
5
19
0
Order By: Relevance
“…J. Agron., 14 (3): 158-163, 2015Mildford et al (1985 reported that light interception is mainly influenced by leaf area index and Scott and Jaggard (1978) had earlier reported that dry matter yield was proportional to the total amount of radiation intercepted by the crop for growth. Total biomass production of a crop, without water limitations, is the product of solar radiation intercepted by the crop canopy over the duration of the cropping period and the efficiency at which the crop converts light energy into plant dry matter (Richards, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…J. Agron., 14 (3): 158-163, 2015Mildford et al (1985 reported that light interception is mainly influenced by leaf area index and Scott and Jaggard (1978) had earlier reported that dry matter yield was proportional to the total amount of radiation intercepted by the crop for growth. Total biomass production of a crop, without water limitations, is the product of solar radiation intercepted by the crop canopy over the duration of the cropping period and the efficiency at which the crop converts light energy into plant dry matter (Richards, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…5 shows an S-shaped relationship for leaf area with accumulated temperature above this base temperature. This is because final areas of individualleaves vary systematically with their position on the plant, increasing up to leaves 9 to 12 and then decreasing (Milford et al 1985b). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sugar accumulation is inversely related to nitrogen uptake (Werker et al, 1999). On the other hand, nitrogen deficiency affects leaf expansion (Milford et al, 1985), thus decreasing photosynthetic assimilation and crop yield. Therefore, a compromise has to be reached.…”
Section: Introductionmentioning
confidence: 99%